Breaking the Path to Contextual Music Education: A Pedagogical Biography of Dirwan Wakidi and His Contribution to the Development of the Discipline in West Sumatra - rahma, azzahra ashila; Hendri, Yon; Awerman, Awerman; Yusnelli, Yusnelli; Wijaksana, Bambang (Scoring: Journal of Film Music, 2025)
Individual biographies in the context of arts education play a crucial role in uncovering pedagogical practices, teaching philosophies, and contributions to the development of the discipline. This journal article presents an in-depth biographical study of Dirwan Wakidi, an influential music teacher in Indonesia, focusing on his unique contributions to music pedagogy and curriculum development. This study employs qualitative methods through an oral history approach, in-depth interviews with students, colleagues, and family, analysis of personal archives (teaching notes, musical compositions, learning programs), and participant observation within his teaching environment. The research findings reveal three key contributions of Dirwan Wakidi: (1) The development of a “Music for All” pedagogical model that integrates local wisdom values with contemporary music techniques, thereby enhancing the relevance and accessibility of music education; (2) His role as a catalyst in building a collaborative music education ecosystem at the regional level, which has impacted on enhancing the capacity of other music teachers; and (3) The formulation of a context-based music curriculum framework that emphasizes creativity, self-expression, and cultural appreciation, in addition to mastery of techniques. This study concludes that Dirwan Wakidi's biography not only captures a personal narrative but also reflects the broader dynamics of the history of music arts education in Indonesia, offering a model for contextual and sustainable teaching practices. The implications of this research provide a theoretical foundation for the development of inclusive music arts pedagogy and policy recommendations for arts teacher training oriented toward local strengths. This research fills a gap in the literature by documenting and analyzing the practice of an arts education practitioner whose work is significant but has not been academically documented in leading journals.